The Effect of Individual Characteristics, Physical Activity, and Consumption of Sweetened Foods and Drinks on the Incidence of Type 2 Diabetes Mellitus in Adults Aged 30-60 Years in Medan - Icmi Ikhtiari Nanjar; Fazidah Aguslina Siregar; Sri Rahayu Sanusi (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
The Sustainable Development Goals (SDGs) aim to reduce morbidity and mortality from non-communicable diseases, including diabetes mellitus, by 2030. Around 8.5 percent of adults worldwide are living with of type 2 diabetes mellitus, and up to 1.5 million people die from it. The prevalence of diabetes mellitus in Indonesia was 2 percent in 2018, and in North Sumatera was 249.519 cases with the highest number of cases in Medan City. This increase in diabetes mellitus prevalence is associated with several risk factors. This study aims to analyze the effect of individual characteristics, physical activity, and consumption of sweetened foods and drinks on the incidence of type 2 diabetes mellitus in 30-60 years age group in Medan. This type of research was observational analytic used a case control design. This study was conducted in 6 community health centers with the highest number of diabetes cases divided into 3 sub-districts with the highest number of type 2 diabetes mellitus cases. This study was conducted from February to October 2023. The sampling technique uses purposive sampling. The population in this study were people 30-60 years age group in Medan with sample size of 66 cases and 66 controls. Logistic regression was used for data analysis. The results showed that there was an effect between age (p=0.002), physical activity (p=0.034), consumption of sweetened foods and drinks (p=<0.001), and family history (p=<0.001) on the incidence of type 2 diabetes mellitus. The community is expected to do regular physical activity of at least 150 minutes per week, limit sugar intake every day, and conduct regular health checks if they know the family health history that contributes to the development of type 2 diabetes mellitus.Keywords: Diabetes, Drinks, Foods , Physical Activity, Sweetened